Mathematics and Gender Stereotypes in One Jewish and One Druze Grade 5 Classroom in Israel. (2nd June 2011) - Mittelberg, David; Rozner, Osnat; Forgasz, Helen
Abstract : We report findings from qualitative case studies of two grade 5 classrooms in Israel, one Jewish and one Druze. The aim was to identify classroom factors contributing to the differences in the gendered patterns of mathematics outcomes for Jewish and Arab Israeli students. Marked differences were found in the teachers' gender-related interactions with students, and their beliefs and expectations of boys' and girls' mathematical capabilities. The Jewish teacher held conventional gender-stereotyped beliefs of male mathematical superiority. The Druze teacher believed that girls required affirmative action to overcome implied gender biases in favour of males in the Druze community. The findings support earlier research and theoretical perspectives on gender-related issues in the mathematics classroom. In particular, when teachers hold gender-biased beliefs and expectations, students' classroom experiences and mathematics learning outcomes are impacted along gender lines.